Citra Tubuh, Pengetahuan, Sikap dan Tingkat Aktivitas Fisik Mahasiswa pada Masa Pandemi Corona Virus Disease 2019 - Perdinan Managkabo; Barnabas Harold Ralph Kairupan; Aaltje Ellen Manampiring (Universitas Sam Ratulangi, 2021)
Background: The World Health Organization (WHO) declared the corona virus outbreak a global pandemic on March 11, 2020. Countries in the world affected, including Indonesia. All activities outside the home are limited, including physical activity. Citra tubuh, knowledge, and attitude are factors affecting physical activity. The purpose of this study was to see the correlation between citra tubuh, knowledge, and attitudes with the level of physical activity among students of the Faculty of Public Health, Sam Ratulangi University (FKM UNSRAT) during the Covid-19 pandemic. Methode: This research uses a quantitative approach, with survey methods and associative analysis techniques (correlational). The sampling technique was purposive sampling. This research was conducted at FKM Unsrat students with an interest in Occupational Health and Safety (K3) in January 2021. The sample in this study was 60 students from the total population. The variables of this research are physical activity as the dependent variable, citra tubuh, knowledge, and attitude as independent variables. Questionnaire as a measuring tool. The research data were analyzed by univariate and bivariate with the chi-square test. Data presentation is made in table and narrative form. Result: The results showed that citra tubuh with sufficient physical activity was in the satisfied category, namely 92%, good category knowledge with sufficient physical activity was 85%, good category attitude with adequate physical activity was 80%. Bivariat analysis was showed that there are correlation between citra tubuh, knowledge, and attitudes with the level of physical activity among students of the FKM UNSRAT during the Covid-19 pandemic. Conclusion: The conclusion of this study is that the citra tubuh, knowledge, and attitudes were the factors correlated with the level of physical activity among students of the FKM UNSRAT during the Covid-19 pandemic.